From Allies to Adversaries: The potential impacts of the Russian-Ukrainian crisis on Russian-Indian relations - Saaida, Mohammed B. E. (The Greek Review of Social Research, 2024)
This study presents the impact of the Russian-Ukrainian conflict on the relationship between Russia and India, finding that both countries remain committed to maintaining good relations despite challenges posed by the conflict and economic sanctions. The article explores several scenarios for the future of Russian-Indian relations and suggests that the most likely scenario is that relations will remain positive and productive based on shared interests and strategic partnerships. The study highlights the importance of continued research on the relationship between Russia and India and suggests areas for future research.